Analisis Perencanaan Pembelajaran Berbasis Praktik Baik sebagai Strategi Peningkatan Kualitas Pembelajaran di Madrasah Tsanawiyah Assalaam - Syifa Delfiani Gunawan; Mulyawan Safwandy Nugraha (TADRIBUNA: Journal of Islamic Education Management, 2026)
This study aims to analyze the structure of best-practice-based educational planning at MTs Assalaam and its contribution to improving instructional quality. A qualitative case study approach was conducted at MTs Assalaam through in-depth interviews with the principal, vice principal for curriculum affairs, teachers, and educational staff, supported by participant observation and analysis of school planning documents. The findings reveal that best practices emerge from teacher reflection, collaborative lesson planning, active learning, and academic supervision. These practices improve instructional effectiveness, strengthen the relevance of annual planning, and promote teacher engagement and program implementation consistency. In addition, best-practice-based planning fosters a collaborative and adaptive work culture. However, some best practices remain undocumented and therefore have not been fully utilized as a basis for institutional decision-making.